RELATIONSHIP OF SELECTED PRENATAL FACTORS TO PREGNANCY OUTCOME AND CONGENITAL ANOMALIES - Qazi, Gulrukh (Journal of Ayub Medical College Abbottabad, 2010)
Objective: The aim of this paper is to explore the relationship of various selected prenatal circumstances to pregnancy outcome in particular reference to congenital anomalies. Method: It was a cross-sectional analytical study and conducted at unit ’˜A’ of the Department of Obs/Gyn, Postgraduate Medical Institute, Lady Reading Hospital, Peshawar, from January to December 2009. The analysis included data on all women having pregnancies with adverse outcome and various congenital anomalies during the study period 1st January to 31st December 2009. A hospital-based maternal health data was used from history records and direct interviewing of the patients subject to their availability and information were recorded for all the cases on structured proformae. The data included demographic details, social environment, consanguinity, ovulation induction, drug intake during early pregnancy, exposure to radiation, infection during early pregnancy, complications of pregnancy, prematurity, obstetrical variables, congenital anomalies and materno-foetal morbidity and mortality. Findings at prenatal visits and data regarding prior pregnancies and morbidity among other children are also abstracted from obstetrical and medical charts. In case of the newborn, the neonatal chart abstract has proved to be a more complete source of information on congenital anomalies. The data was entered on SPSS-10 and the analysis included simple proportions and rates. Results: Out of a total of 5,082 deliveries 163 (3.2%) were complicated by various congenital anomalies with prepondrence of neural tube defects notably the hydrocephalous (33.4%) and Anencephaly (29.2%). Most of the mothers were un-booked and uneducated (90%). Eighty- eight (54%) women were in there twenties, thirty (22%) with ‰¥35 years of age and only 9%in the teenage group. About 36% of the deliveries in the study population are among primigravida. Four cases (3.1%) had history of exposure to some non-specific radiation due to the locality of there house. Almost 21% of couples had cousin marriage. Regarding drug intake no specific link could be demonstrated as 45% took nothing while the remaining took the multivitamins and tonics only. Only 4 cases (2.5%) had taken assisted conception in the form of clomiphene citrate. About 34 per cent of the multigravida with antepartum bleeding reported that their last prior pregnancy ended in a foetal death or prematurely born infant. The corresponding figure for all multigravida women was 21 per cent. However, prior pregnancy history does not explain the more adverse risk associated with APB. Conclusion: These results together provide information to physicians and genetic counsellors to realise contribution of congenital abnormalities and setting priorities of screening individual cases. Keywords: Outcome, Prenatal, Pregnancy, Foetal, Counselling